Intestinal intussusception due to “Rapunzel syndrome” in an adult - Gómez Alan, Guerrero; Mariela Itzayana, López Alvarado (International Journal of Research in Medical Sciences, 2023)
The bezoars are collections of foreign bodies or ingested material that accumulate over time and are often located in the stomach or small intestine,but can be found throughout the digestive tract. Most bezoars are of indigestible organic matter such as trichobezoars (hair); or vegetable and fruit- phytobezoars; or a combination of both but other rare substances have also been described in literature. In some cases, the trichobezoar extends through the pylorus into duodenum, jejunum or even into the colon. Rapunzel syndrome is a rare manifestation of a trichobezoar, which occurs when strands of swallowed hair extend beyond the pylorus of the stomach, into the intestine as a tail. It was first described by Vaughan et al in 1968. Trichobezoars can block the intestinal tract and, if left untreated, can be a life-threatening emergency requiring surgery. Patients are often women, under the age of 20 and have insidious non-specific abdominal symptoms and staggered presentations over months to years. The diagnosis of this type of pathology is usually a challenge for the attending physician, so we present a case report of a 38-year-old female with gastric-intestinal occlusion secondary to trichobezoar.